Analisis Store Image dan Service Quality dalam Meningkatkan Kepuasan Konsumen - Wulan Puspitasari; Erry Sunarya; Asep M Ramdan (Journal of Management and Bussines (JOMB), 2019)
The research was aimed at determining the influence of store image and service quality in increasing customer satisfaction. The research methods applied were descriptive and associative with quantitative approach. The sampling technique applied was probability sampling by means of simple random sampling approach. The amount of samples deployed were amount to 186 respondents. The technique of analyzing data applied was multiple linear regression analysis technique with the help of SPSS 24 application.The results of the research show that the influence of store image was positive and significant towards customer satisfaction which is amounted to 0.743; thus, the influence of service quality is also positive and significant towards customer satisfaction which is amounted to 0.787. Subsequently, the result conveys that the influence of store image and service quality is aggregated to 65.6% and the epsilon or namely the remaining independent influence caused by other variables not explained in the research is aggregated to 34.4%. Conclusion, there is a positive and significant effect between store image and service quality on consumer satisfaction Keywords: Store Image, Service Quality, Customer Satisfaction